Population changes of plant-parasitic nematodes associated with cover crops following a yam (Dioscorea rotundata) crop - Claudius-Cole, A.O.; Fawole, B.; Asiedu, Robert (Springer, 2015)
Effective management of plant-parasitic nematodes affecting yams includes practices that can break the pest cycle from field to store. This study evaluated nematode population changes under cover crop cultivation following a main yam crop. Ten cover crops were planted after the harvest of the yam crop, in six different yam plots under natural nematode infes- tation. Soil and root samples were collected quarterly for nem- atode analysis from planting time for 12 months. Nematode data obtained were used to calculate prominence values as well as frequencies of occurrence for the nematode species identified. Statistical analyses was by ANOVA and Newman Keuls. Helicotylenchus spp. were the most frequently encoun- tered and prominent nematodes followed by Pratylenchus spp. and Scutellonema spp., while Meloidogyne spp. ranked sixth in prominence. The most effective cover crops were Ta ge te s e re ct a , Aeschynomene histrix , Mucuna pruriens and Pueraria phaseoloides which reduced populations of the four aforementioned nematodes by 70, 39, 20, and 11 %, respec- tively. Lablab purpureus and Cajanus cajan hosted signifi- cantly higher nematode populations in their roots and rhizo- sphere soil samples than other cover crops. Populations of Meloidogyne were reduced with A. histrix, T. erecta, Crotalaria ochroleuca, Crotalaria juncea, P. phaseoloides, and M. pruriens .However,populationsof Scutellonema and Pratylenchus were reduced with A. histrix, T. erecta, P. phaseoloides ,and M. pruriens